2019
DOI: 10.1051/0004-6361/201935359
|View full text |Cite
|
Sign up to set email alerts
|

MONOS: Multiplicity Of Northern O-type Spectroscopic systems

Abstract: Context. Multiplicity in massive stars is key to understanding the chemical and dynamical evolution of galaxies. Among massive stars, those of O type play a crucial role due to their high masses and short lifetimes. Aims. MONOS (Multiplicity Of Northern O-type Spectroscopic systems) is a project designed to collect information and study O-type spectroscopic binaries with δ > −20 • . In this first paper we describe the sample and provide spectral classifications and additional information for objects with previ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 116 publications
(135 reference statements)
1
43
0
Order By: Relevance
“…We find wind variability in the IACOB/OWN spectroscopy, which could be partly responsible for (or caused by) the observed photometric variability. HD 37041 (O9.5 IVp, Sota et al 2011) was found to be a SB2 with a secondary B0.5 V star by Maíz Apellániz et al (2019). We find it as SB1 in the IACOB/OWN spectroscopy.…”
Section: Appendix B5: Binariesmentioning
confidence: 56%
“…We find wind variability in the IACOB/OWN spectroscopy, which could be partly responsible for (or caused by) the observed photometric variability. HD 37041 (O9.5 IVp, Sota et al 2011) was found to be a SB2 with a secondary B0.5 V star by Maíz Apellániz et al (2019). We find it as SB1 in the IACOB/OWN spectroscopy.…”
Section: Appendix B5: Binariesmentioning
confidence: 56%
“…The combined mass of the system exceeds 250 M ⊙ . Even though most stars are found in binaries or higher-order systems (Sana et al 2012(Sana et al , 2013Maíz Apellániz et al 2019), it is still possible that in some rare cases a system like Mk34 merged during the formation process or on the MS and formed a single very massive star exceeding 200 M ⊙ .…”
Section: Initial Mass Function and Upper Mass Limitmentioning
confidence: 99%
“…As AE Aur and ι Ori are both early‐type stars with spectral types of O 9.5 V (Sota et al 2011) and O 8.5 III (Maíz Apellániz et al 2019), their RVs were determined by measuring the wavelengths of the neutral helium lines (He I) at 4713.15, 4921.93, and 5015.68 Å, which were selected based on their prominence in the fully reduced FLECHAS spectra of both stars, the spectral energy distribution of the observed targets, and the spectral sensitivity of the used instrument, respectively.…”
Section: Rv Measurementsmentioning
confidence: 99%